2014
DOI: 10.1007/s10120-013-0328-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trials in patients with relapsed, advanced upper gastrointestinal carcinomas: experience in a specialist unit

Abstract: achieved RECIST-objective response (11 %) with a 6-month clinical benefit rate of 14 %. Median progression free and overall survival were 7.7 weeks [95 %CI 7.7 (6.4-9.0)] and 19.1 weeks (95 %CI 17.5-20.8), respectively. Grade 3 or 4 toxicities were observed in 37 patients (39 %) and led to trial discontinuation in 9 (9 %); no toxicity-related death was recorded. In the multivariate analysis, serum albumin (\35 g/dl, HR2.0, p = 0.002) and lactate dehydrogenase ([192 lmol/l, HR1.7, p = 0.016) were prognostic of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…The 75.7 % of patients with grade 3 or 4 adverse events is considerably higher than reported by previous analyses (19.7-39 %) [15,16]. A reasonable explanation is that the main NCI-CTEP-sponsored phase 1 trials for EGC were for combinations with biologic and cytotoxic agents.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…The 75.7 % of patients with grade 3 or 4 adverse events is considerably higher than reported by previous analyses (19.7-39 %) [15,16]. A reasonable explanation is that the main NCI-CTEP-sponsored phase 1 trials for EGC were for combinations with biologic and cytotoxic agents.…”
Section: Discussioncontrasting
confidence: 45%
“…However, the impact of phase 1 treatment on safety and efficacy for patients with EGC has not yet been evaluated in a large population. Although the prognostic variables for OS have been analyzed [15], the usefulness of the RMH prognostic score for EGC patients has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase I clinical trials are traditionally considered as a means of establishing the maximum tolerated dose of anticancer therapies. However, with the advent of molecularly targeted therapeutics and mapping out of the underlying biology of different cancers and antitumor agents, they may now represent bona fide trial options that may be of benefit, subgroups of patients who have failed all standard available anticancer therapies irrespective of their age ( Khan et al , 2014 ). The lack of representation of older patients with advanced cancers in clinical trials is widely reported ( Hutchins et al , 1999 ; Talarico et al , 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our series was in agreement with these established findings; additionally we found that low albumin and abnormal platelet count were prognostic of worse outcome for both PFS and OS. Abnormal platelet count has been considered as an important prognostic factor in CRC based on the data from UK COIN study [ 30 ], whilst we have previously reported an association of abnormal albumin with poor outcomes in upper GI cancers [ 31 ].…”
Section: Discussionmentioning
confidence: 99%